Dispute Resolution and Self-Selection : An Empirical Examination of the Federal Public Sector, 1971-1982 - Swimmer, Gene; Winer, Stanley (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1993)
Unions in the Canadian federal public service have been able to unilaterally select whether any impasse in the upcoming negotiations would be resolved by a strike or arbitration. In this paper, the union's dispute resolution choice is modelled simultaneously with wage determination in the federal public service, using the self selection methodology.